Floral structure for textile-based metamaterial absorber - Siti Nurzulaihan Isa; Osman Ayop; Farid Zubir; Noor Asniza Murad; Mohammad Kamal A. Rahim (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
Based on an annulled circle structure metamaterial absorber (MMAb), a floral structure MMAb design is proposed for performance improvement especially on absorptivity. Since the initial purpose of designing the MMAb is for hiding one’s existence from electromagnetic motion detector, it is expected that the MMAb will has flexibility as one of its characteristics. The MMAb composes of textile-based substrate in between floral structure at the top and ground plane at the bottom, based on metallic plate. The targeted center frequency is 10.525 GHz and through series of simulation done in CST Microwave Software, the MMAb can reach up to 97.03% of absorptivity. The operating angle can be extended at least 68o before its absorptivity deteriorated below 80%. In addition, the proposed MMAb has a high absorptivity regardless of the polarization angle of the electromagnetic waves.